Matrix Material Learning Design Using Context of Bookshelf to Support High School Students Understand Concepts - Trisna Wulandari; Zulkardi; Ely Susanti; Meryansumayeka Meryansumayeka (Universitas Teknokrat Indonesia, 2025)
Understanding concepts is something that students need to have because concepts in mathematics are interrelated with each other. The purpose of this study was to determine the learning design on matrix material using the concept of bookshelves (lockers) that can support the understanding of the matrix concept of high school students. The researcher designed a student activity sheet with the context of bookshelves (lockers) that are often found in the school environment that are used in learning. The subjects of the study were 35 high school students in grade XI at SMA Srijaya Negara Palembang. The research method used was design research through three stages, namely the preparation for the experiment, the design experiment, and retrospective analysis. Data collection through the results of student activity sheets and interviews. The data collected were analyzed descriptively. This study produced Hypothetical Learning Trajectory (HLT) which can support student understanding to the concept of matrices.